Pengaruh Daya Tarik, Citra Destinasi dan Persepsi Harga Terhadap Keputusan Berkunjung ke Taman Safari Bogor - Nisrina Rohaina Suparman; Leonardo Indra Vitaharsa (Panorama Nusantara, 2022)
This study aims to determine and analyze the effect of attractiveness, destination image and price perception on visiting decisions. The population in this study was 100 respondents with data collection using a questionnaire given to respondents with accidental sampling technique. The analytical method used in this research is multiple regression analysis. The results of this study indicate that the attractiveness variable, destination image variable, and price perception variable simultaneously influence the decision to visit the Bogor Safari Park. Then the partial results show that the destination image variable and price perception have a significant effect on the decision to visit, while the attractiveness variable has no effect on the decision to visit.